2018
DOI: 10.1186/s13104-018-3396-4
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and gestational weight gain in the Norwegian Fit for Delivery trial

Abstract: ObjectiveExcessive gestational weight gain is linked to risk of preeclampsia, but it is not clear whether the association is causal. The purpose of this paper was to examine gestational weight gain in the Norwegian Fit for Delivery study among women who developed preeclampsia compared to those who did not, and to further explore associations between weight gain and preeclampsia by including data on body composition (bioimpedance) assessed in the last trimester of pregnancy.ResultsA total of 550 women were elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
1
17
0
7
Order By: Relevance
“…Speci cally, excessive GWG in the pre-pregnancy overweight and obese mothers was signi cantly associated with increased risk of PE. This is in keeping with the ndings reported by previous works (31,32). This nding was also appreciated for MPE and LOPE (6,33).…”
Section: Discussionsupporting
confidence: 92%
“…Speci cally, excessive GWG in the pre-pregnancy overweight and obese mothers was signi cantly associated with increased risk of PE. This is in keeping with the ndings reported by previous works (31,32). This nding was also appreciated for MPE and LOPE (6,33).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed that gestational weight gain (GWG) was important in predicting GH compared to pre-pregnancy BMI, but GWG may be associated with fluid retention, and this clinical factor had limited predictive value [ 7 , 31 , 32 ]. In our cohort, the percentage of women with GWG above the IOM recommendation range was 36.8%, but for the women with excessive pre-pregnancy BMI, it was 59.0%.…”
Section: Discussionmentioning
confidence: 99%
“…BIA has been used in various clinical situations and pre-pregnancy and pregnancy conditions, including oedema [60], GDM [48,50,51,61,62], excessive gestational weight gain (EGWG) [2,3,48,51,52,55,57,[62][63][64][65], preeclampsia (PE) [57,60,[66][67][68][69][70][71][72][73][74], gestational hypertension (GH) [73,75] or hyperemesis gravidarum [76]. Hashimoto et al compared the impedance analysis in healthy women and in women undergoing haemodialysis whose management of bodily fluids during pregnancy is known to be complicated [35].…”
Section: Pregnancymentioning
confidence: 99%